Makerspaces for Newcomers' Language and Literacy Learning - Yina Liu (Canadian Society for Studies in Education, 2020)
In this paper, I present ways that makerspaces could support children's language and literacy learning and engage young participants in this digital age. In addition, I argue that makerspaces could be a place for newcomer children to embrace their funds of knowledge (Moll et al., 1992) and use them as a foundation to language and literacy learning.